(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this study, Xanthan gum (xg), tamarind gum (TG), and fenugreek gum were used to create a sustained release matrix tablet of nifedipine (NFD). With different ratios of drug and polymer, sustained release tablets were created using the direct compression method. When creating the formulation for sustained release, drug and polymer ratios were optimized. A drug release formulation that was optimized for time was discovered. Three different rate-controlling materials combined with a triple mixture of two additional rate-controlling materials were used to modulate the release rates. For the dissolution rate study, 0.1N HCl pH 1.2 was used for two hours, followed by 12 hours in phosphate buffer pH 6.8. We observed and took note of the effects of three different polymer concentrations as well as polymer blend concentration. Using the Higuchi expression, the data on dissolution was examined. Sustained release matrix tablets that contained a polymer blend of Xanthan gum, Tamarind gum, and Fenugreek gum were found to successfully sustain the release of medication for up to 12 hours. Formulation F3 contained 25% fenugreek mucilage and 20% xanthan gum, respectively, out of all the prepared formulations. By way of diffusion, erosion, and release, the drug's release rate conforms to Higuchi kinetics. In comparison to other batch products that had been prepared, the profile of formulation F3 was appropriate and strong.